Pengaruh Stimulasi Media Permainan Playdough Terhadap Perkembangan Motorik Halus Anak Usia 54-59 Bulan - Sa'deyah, Zusniyah Khalimatus; Mudlikah, Siti (IJMT : Indonesian Journal of Midwifery Today, 2024)
Background: Child development determines the quality of life at the next stage. Child development disorders are influenced by many factors: stimulation, nurturing environment, nutrition, socio-economics, genetics and other factors. The aim of this research was to determine the effect of playdough media stimulation on children's fine motor development. Methods: Quantitative with experiments, one group pre-post design. The population of all Muslimat NU 166 Kindergarten children aged 54-59 months is 35 children, the total sample is 32 children. Simple random sampling technique, stimulation assessment instrument, checklist observation sheet and assessment of KPSP development according to the child's age. Results: The development of children's fine motor skills before being given playdough game stimulation was in the highest category according to 23 children (71.9%), and after being given playdough game stimulation all categories were according to 32 children (100%) in the KPSP assessment. Wilcoxon Test Analysis Asymp value. Sig (2-tailed) obtained a value of P = 0.003 (p < 0.05). Conclusion: There is a stimulating effect of playdough media on the fine motor development of children aged 54-59 months at the Muslimat NU Nahdlatul Ummah Golokan Sidayu Gresik Kindergarten.